Protective effect of Cordia boissieri A. DC. (Boraginaceae) on metabolic syndrome - Asmaa I. Owis, Amira M. Abo-youssef, Ahmed H. Osman (Journal of Applied Pharmaceutical Science, 2016)
Increased fructose ingestion has been linked to obesity, hyperglycemia, dyslipidemia, and hypertension associated with metabolic syndrome. Cordia boissieri A. DC. (Boraginaceae) is a slow growing beautiful plant, used traditionally as herbal remedy by diabetic Hispanic women in the Southwestern USA. The present study aimed to elucidate the toxicity and the possible protective effect of ethyl acetate extract of C. boissieri leaves on metabolic syndrome. Three groups of rats were fed on fructose-enriched diet for 14 weeks. One group served as fructose-enriched diet control, while the remaining groups were treated with metformin (10 mg/kg/day) and ethyl acetate extract (200 mg/kg/day) during the last 4 weeks. A fourth group was fed on normal laboratory diet. At the end of the experiment, blood samples were withdrawn for the estimation of metabolic syndrome-related markers and liver samples were subjected to histopathological and immunohistochemical examination. Induction of metabolic syndrome using fructose enriched diet was associated with increased weight gain coupled with elevated levels of blood glucose, insulin, uric acid, urea, creatinine, total cholesterol, triglycerides, malondialdehyde (MDA), nitric oxide and tumor necrosis factor in addition to, decreased level of glutathione (GSH). Four-weeks oral administration of ethyl acetate extract attenuated most of the changes associated with metabolic syndrome as marked by improved insulin sensitivity, glucose tolerance, kidney function, lipid profiles and reduced oxidative stress and inflammation. The present study provides evidence of the potential protective effect of C. boissieri against metabolic syndrome.
Keywords: Cordia boissieri, Boraginaceae, metabolic syndrome, ethyl aetate.